ROLE OF EDUCATIONAL HADITHS IN BUILDING ISLAMIC ‎EDUCATIONAL ETHICS IN ‎THE DIGITAL ERA - Sari, Misalia; Husnilawati, Husnilawati; Gani, A; Akmansyah, Muhammad; Abas, Erjati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid advancement of digital technology has significantly transformed the landscape of education, including Islamic education. While offering opportunities to expand access to knowledge, the digital era also presents ethical challenges such as character degradation, academic dishonesty, and weakened spiritual engagement. This study aims to conduct an in-depth analysis of the role of educational hadiths in shaping and reinforcing Islamic educational ethics in the digital age. Employing a qualitative approach through literature review and thematic analysis, this research explores selected prophetic traditions that emphasize values such as honesty, responsibility, adab (etiquette) in learning, and information verification (tabayyun). Data were collected from classical hadith sources and relevant scholarly publications from the last decade. The findings indicate that educational hadiths remain contextually relevant and can serve as a moral compass for addressing digital-age challenges. The integration of hadith values into digital curricula and learning platforms not only strengthens students’ ethical awareness but also promotes balanced spiritual and intellectual development. The study recommends the development of structured hadith-based learning models and the evaluation of their effectiveness within digital learning environments such as Learning Management Systems (LMS) and Islamic educational applications. Furthermore, collaboration among educators, parents, and policymakers is crucial to ensure the sustainable internalization of prophetic values among Generation Z learners. This research contributes both theoretically and practically to the discourse on Islamic education and digital ethics.